Jerome Titlow papers - Titlow, Jerome
Letters to Titlow from Varina Davis and Margaret Howell Davis Hayes and clippings concerning the shackling of Jefferson Davis at Fort Monroe, Va., in which Titlow participated.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Davis, Jefferson, -- 1808-1889 -- Captivity, 1865-1867.; Davis, Varina, -- 1826-1906 -- Correspondence; Hayes, Margaret Howell Davis, -- 1855-1909 -- Correspondence; Fort Monroe (Va.) -- History; Army officers